Peningkatan Hasil Belajar Qs Ali-Imran: 64 Dan Qs Al-Baqarah: 256 Melalui Metode Make a Match Pada Siswa Kelas 5 SDN 12 Koto Tinggi Kec. Lubuk Sikaping Kabupaten Pasaman - Zuwarti, Devi (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aimed to examine the effectiveness of implementing the Make a Match model combined with Project Based Learning (PBL) in improving students’ learning outcomes in Islamic Education, specifically in understanding Surah Ali Imran: 64 and Surah AlBaqarah: 256. This classroom action research was conducted on [grade] students at [school]. The results showed that the combination of both learning models had a positive impact on improving students’ conceptual understanding, learning motivation, and skills. Students became more active, enthusiastic, and able to apply the values contained in the Qur’an in their daily lives. These findings indicate that the Make a Match and PBL learning models can be an effective alternative to improve the quality of Islamic education.